Virtual Reality Untuk Penyintas Stroke: Tinjauan Sistematis Rehabilitasi Motorik, Kognitif, Dan Psikososial - Hidayat, Anisa; Renata, Zetta Putra; Novitasari, Dwi; Ma'rifah, Atun Raudotul (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
Background: Stroke is a leading cause of long-term disability worldwide, resulting in motor, cognitive, and emotional impairments. Rehabilitation is a crucial aspect of post-stroke recovery, improving function and quality of life. In recent years, virtual reality (VR) has emerged as a complementary innovation to conventional therapy. This technology offers an interactive environment specific to rehabilitation tasks, stimulating neuroplasticity and increasing patient motivation during therapy. Numerous studies have shown that VR can provide engaging and adaptive therapeutic experiences tailored to individual needs, both for the recovery of motor function, balance, and psychosocial aspects. Commonly used VR platforms include Wii Fit, Xbox Kinect, immersive VR headsets, and systems integrated with exoskeletons. Various studies have shown that VR-based interventions improve motor function (Fugl-Meyer, ARAT), balance (BBS, TUG), and psychological well-being (decreased depression and increased motivation). However, the effectiveness of VR is still affected by heterogeneity in study designs, small sample sizes, and variations in outcome measures. Despite this, most patients report high levels of satisfaction and comfort during therapy. Therefore, further trials using standardized methods are needed to ensure the effectiveness and feasibility of implementing VR in interdisciplinary stroke nursing and rehabilitation practice.